1981
DOI: 10.1007/bf00283674
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous haemoglobin constant spring: A need for revision of concept

Abstract: Twenty-two patients with mild haemolytic anaemia and haemoglobin (Hb) Constant Spring (CS) of around 6% were studied because they were suspected of having homozygous Hb CS. Family studies revealed Hb CS trait in both parents of eight patients, supporting that they were homozygous for Hb CS. The other patients were included because they had clinical and haematological features similar to the diagnosed cases of homozygous Hb CS. Heterozygosity and homozygosity for Hb CS are clearly distinguishable in that the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…However, HbCS homozygotes are not phenotypically the same as a4-thalassemia homozygotes. The findings in the HbCS homozygote described here are identical to those previously described (6,8,9 After transcription of the acs-gene (whether this is at a normal or subnormal level is not yet known) there is instability of the acsamRNA, which decreases during erythroid maturation and which is virtually absent from reticulocytes (3,30). The synthesis of C-chains follows the same pattern, decreasing from bone marrow to reticulocytes (2, 31); but once incorporated into a hemoglobin tetramer, the aCs-chains seem to be quite stable in vivo.…”
Section: Hematologic Studiessupporting
confidence: 91%
See 3 more Smart Citations
“…However, HbCS homozygotes are not phenotypically the same as a4-thalassemia homozygotes. The findings in the HbCS homozygote described here are identical to those previously described (6,8,9 After transcription of the acs-gene (whether this is at a normal or subnormal level is not yet known) there is instability of the acsamRNA, which decreases during erythroid maturation and which is virtually absent from reticulocytes (3,30). The synthesis of C-chains follows the same pattern, decreasing from bone marrow to reticulocytes (2, 31); but once incorporated into a hemoglobin tetramer, the aCs-chains seem to be quite stable in vivo.…”
Section: Hematologic Studiessupporting
confidence: 91%
“…Autohemolysis showed 1.40 and 3.35% lysis after 48 h with and without glucose, respectively. The whole-blood oxygen dissociation curve was shifted left slightly, with an oxygen pressure at 50% Hb saturation of 24.5 mmHg (control 29.0 mmHg) and a 2-3-diphosphoglycerate level of 6.55 mmol/liter.…”
Section: Hematologic Studiesmentioning
confidence: 96%
See 2 more Smart Citations
“…In accordance with these findings in South East Asian populations, several studies indicated that the (acsa) haplotype, containing the Constant Spring muta tion in the a 2-gene results in a more severe phenotype than that associated with the (-a) haplotype [25]. Infants with the (acsa/aa) genotype, in fact, produce more Hb Bart's at birth than those with the (-a/aa) genotype, sub jects with the (-/a csa) genotype have a severer form of HbH disease than those with the (-/-a) genotype and fi nally, individuals homozygous for the Constant Spring mutation (a^a/a^a) showed a severer phenotype than the a-carriers [25,26].…”
Section: Discussionmentioning
confidence: 99%